Performance of The Head of Homeschooling: The Influence of Transformational Leadership, Motivation and Self-Efficacy - Afzal Sayed Munna; Duratul Ain Tholibon; Denok Sunarsi; Dodi Ilham; Muh Rizal (Jurnal Ilmiah Sumber Daya Manusia, 2022)
This study aims to analyze the relationship of transformational leadership, motivation and self-efficacy to the Head of homeschooling performance. This research method is quantitative with data processing tools using SPSS software. Data were obtained through the distribution of online questionnaires to 212 homeschooling teachers in Tangerang who were selected using the simple random sampling method. Based on data analysis, it can be concluded that transformational leadership has a positive effect on the head of homeschooling performance, motivation has a positive effect on the head of homeschooling performance, self-efficacy has a positive effect on the head of homeschooling performance and transformational leadership, motivation and self-efficacy simultaneously have a positive and significant effect on head of homeschooling performance.